Duas sendas do discurso psicótico em O dia em que matei meu pai: esse silêncio... Você ainda está aí? - Versa, Cezar Roberto (2017)
The present term paper produces the Discourse Analysis of a literary work, it was understood like the report of a man who claims to have killed the father. The novel The day I killed my father, by Mario Sabino, constitutes the textual corpus for discursive analysis. The methodology and theoretical basis of this analysis are based on the French School of Discourse Analysis, based on the conceptual assumptions by Michel Pêcheux. In this sense, the opacity of the language, the subjection of the subjects and the cleavage of the unconscious, they transverse the people through discourses. The discourse of madness will be seen from DF (Discourse Formation) of rationality and DF of madness, it was understood as an unreason, in which the effects of meaning are being constructed in this dual game of reason and unreason, of logic and illogical, antinomically way. It was understood this duality, the analytic process developed through two distinct analytical paths. In the first one, the paranoid discourse of a man who committed the murder of the father and he serves a sentence of security measures, this man tries to rationalize at all times the reasons that led to such an act, although it is considered incapable, therefore, in imputable. In the second path, the paranoid discourse is from a man who, within his logic of foreclusion, he constitutes his rationality for the materialization of this fact, of killing the father, at the level of his psychotic discourse, in a movement of decomposition, in which he lacks the paternal function, which eliminates with the murder of this same father. For the composition of these analytical frameworks, theories have been used as criminology and psychoanalysis, taking technical and scientific DF references to law and medicine. The complexity of the definition of rationality in the psychotic discourse was perceived, which happened due to the advent of psychoanalysis. Madness as lack of reason takes place in the most varied DF, yet understanding how logic exists in psychotic discourse enables a differentiated reading of this phenomenon, thanks to the basic concepts of the theories by Freud and Lacan. The great challenge of the two analytical paths of these paranoid discourses we took was to realize that both the condition of production of one who kills the father, in a materialized parricide, and that of a person who does so in the level of his paranoia, these discourses were in ideal of reality at DF levels of rationality, although they are intrinsic to psychotic discourses par excellence.